IMPROVING STUDENTS' ABILITY IN WRITING RECOUNT TEXT THROUGH ELECTRONIC JOURNALING - Ristiani, Desi (2016)
This study was aimed at investigating the effectiveness of electronic journaling implementation to improve students' writing ability especially in writing Recount Text and students' responses toward the implementation of it. The study employed quasi-experimental design by using three instruments namely pretest, posttest, and questionnaire. Seventy two students of Grade VIII in a Junior High School in Bandung participated in the research. The data from pretest and posttest were analyzed by using Coffin's numeric and scoring rubric guide (2004, cited in Emilia, 2011). It was also analyzed by using SPSS 20 for Windows. The results reveal that there was a significant improvement on students' writing in the experimental group after receiving treatment for six meetings. The mean score improved from 43.20 (pretest) to 76.20 (posttest). In addition, the Asymp. Sig (2-tailed) value on independent t-test was 0.000, which was lower than the alpha level (0.05), meaning that there was significant difference between students' posttest scores in the experimental and control groups. Moreover, the score of effect size was 0.73. It was categorized as large size, which means that electronic journaling had a large effect to improve students' ability in writing Recount Text. Furthermore, the findings from questionnaire show that electronic journaling was positively accepted by most of the students. Electronic journaling can easily to be done, can flexibly check teacher's feedback, improve self-confidence in writing, make them easily tell their experiences, improve writing ability especially on vocabularies and grammar; and help students in comprehending Recount Text material. Finally, electronic journaling is recommended to be implemented as a technique in teaching writing.;---Penelitian ini bertujuan untuk menginvestigasi keefektifan dari penerapan menulis jurnal elektronik untuk meningkatkan kemampuan siswa dalam menulis teks Recount dan respon siswa terhadap penerapan jurnal elektronik. Penelitian ini menerapkan desain kuasi eksperimen dengan menggunakan tiga instrumen yaitu pretest, posttest, dan kuesioner. Sebanyak 72 siswa kelas 8 di salah satu Sekolah Menengah Pertama (SMP) di Bandung berpartisipasi dalam penelitian. Data dari pretest dan posttest dianalisis berdasarkan rubrik penilaian Coffin (2004, dikutip dari Emilia, 2011). Kemudian, data tersebut juga dianalisis menggunakan SPSS 20. Hasilnya menunjukkan bahwa terdapat peningkatan yang signifikan pada tulisan siswa dalam kelompok eksperimen setelah menerima perlakuan selama enam pertemuan. Nilai mean kelompok eksperimen meningkat dari 43.20 ke 76.20. Selain itu, nilai 2-tailed pada independent t-test adalah 0.000, yang berarti lebih rendah dari alpha level (0.05). Dengan kata lain, terdapat perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol. Kemudian, nilai dari effect size adalah 0.73, dimana nilai tersebut termasuk dalam kategori efek yang besar. Artinya, menulis elektronik jurnal memiliki pengaruh yang besar dalam meningkatkan kemampuan siswa dalam menulis teks Recount. Di samping itu, hasil dari kuesioner menunjukkan bahwa kegiatan menulis jurnal elektronik dapat diterima secara positif oleh sebagian besar siswa. Menulis jurnal elektronik dapat dengan mudah dilakukan, dapat dengan mudah menceritakan pengalaman, meningkatkan kemampuan menulis siswa terutama dalam hal tata bahasa dan kosakata, membantu siswa dalam memahami materi teks Recount. Dengan demikian, kegiatan menulis jurnal elektronik dapat direkomendasikan untuk diterapkan sebagai teknik dalam pengajaran menulis.